Effect of Lintel Beam on Seismic Response of Reinforced Concrete Buildings with Semi-Interlocked and Unreinforced Brick Masonry Infills - Mangeshkumar R. Shendkar; Denise-Penelope N. Kontoni; Sasankasekhar Mandal; Pabitra Ranjan Maiti; Dipendra Gautam (Infrastructures, 2021)
The primary focus of this study is to evaluate the nonlinear response of reinforced concrete (RC) frames with two types of brick infills viz., unreinforced brick masonry infill (URM) and semi-interlocked brick masonry infill (SIM) together with lintel beams, subjected to seismic loads. The seismic response is quantified in terms of response reduction factor and base shear. Infill walls are modeled using double strut nonlinear cyclic element. Nonlinear static adaptive pushover analysis is performed in the finite element program SeismoStruct. The response reduction factor (R) is computed from adaptive pushover analysis and performance for all models is obtained. The results showed that the average R factor of the RC framed structure with semi-interlocked masonry (SIM) is 1.31 times higher than the RC frame with unreinforced masonry (URM) infill. The R value of the bare frame with the lintel beam is found to be less than the corresponding value recommended in the Indian Standard Code. The results obtained in this study highlight that if the impacts of lintel beams and various brick infill scenarios are considered in the RC frames then the R values used for the design of RC frame buildings with infills would be underestimated (i.e., the evaluated R values are greater than the R values used for the design purpose).